Aktivitas Ekstrak Kasar Enzim Fibrinolitik Bakteri Bacillus cereus yang Diisolasi dari Air Hutan Mangrove Maroon Edupark Semarang secara In Vitro - Rizky Bimantara HA; Ana Indrayati; Desi Purwaningsih (Jurnal Farmasi Indonesia, 2022)
Fibrinolytic enzymes are enzymes that work by degrading fibrin in blood clots. Fibrinolytic enzymes are produced by many organisms, one of which is the bacterium Bacillus cereus from the water of the Maroon Edupark mangrove forest, Semarang. Isolation of fibrinolytic enzymes from bacteria is very important because bacteria are easy to grow, have a fast generation time, do not require a large area for cultivation, and are easily genetically modified so that it will be more economically profitable. In addition, fibrinolytic enzymes from natural ingredients have fewer side effects than synthetic fibrinolytic drugs. This study aims to determine the activity of the crude extract of the fibrinolytic enzyme B. cereus in lysis blood clots in vitro. The study began with confirmation of the presence of genes encoding fibrinolytic enzymes from bacteria B. cereus uses NCBI's popular resources 'nucleotide', identification of bacterial morphology in blood agar media, Gram staining, endospore staining, catalase and coagulase testing. Isolation of crude extract of fibrinolytic enzyme B. cereus is carried out by enzyme extraction. Protein concentration were determined using Bradford method and fibrinolytic activity test in vitro using fibrin plate media with nattokinase as positive control. The resulting clear zone shows the ability of the enzyme extract in degrading fibrin The results of the identification of the B. cereus bacterial gene uses the NCBI data base registered as the AprE gene. The results of the identification of gram and endospore staining, B. cereus is a Gram-positive bacterium and has endospores. Identification of bacteria on blood agar media indicates that B. cereus represents the group of the β-hemolysis. Catalase and coagulase test results show that the bacteria produce catalase and coagulase enzymes. Total protein concentration from crude extract of B. cereus obtained at 19.63 mg/mL. Fibrinolytic activity at concentrations of 20, 40, 80% was 2.54; 6.11; and 7.94 mm respectively. Based on the above results it can be concluded that the crude extract of fibrinolytic enzyme B. cereus has the potential to be developed as a natural fibrinolytic agent.